Does endogenous feline leukemia virus occur as a risk factor?: A molecular characterization study from Türkiye: Molecular analysis of enFeLVs - Koç, BT; Oğuzoğlu, TÇ (Journal of the Hellenic Veterinary Medical Society, 2023)
Feline leukemia virus (FeLV) is a feline retrovirus that causes various effects on cat health. FeLV, along with other retroviruses, has altered in terms of molecular structure and pathogenetic and clinical status due to integration into the host genome. In this study, we aimed to determine the presence of enFeLV in the indoor-cats and provide a comparison with potential exFeLV prevalence. Additionally, we aimed to investigate the relationship between positive cases of enFeLV and risk factors including age, gender, breed. We collected 200 samples from domestic cats in Turkey for molecular diagnosis and characterization of en- or exFeLV. Amplified products were purified and sequenced using the Sanger method. According to the phylogenetic tree, our sequences constituted two main clusters that were divergent from each other in Group-2 enFeLVs. The unit of “Health status” in the overall population comprised 161 healthy and 39 diseased cats according to clinical diagnosis. In diseased cats, 17 were found to be enFeLV positive (17/39; 43.6%). “Gender”, “age”, and “breed” were not found to be risk factors for the presence of enFeLV among domestic cats in this study. With regards to the outcomes of the study, we submit that both variants of FeLV should be tested prior to initiating a vaccination program.